New insights on poly(cis-1,4-isoprene) rubber degradation through enzymatic kinetics and process improvement - Guajardo-Flores, Camila; Rojas, Josefa; Baldera-Moreno, Yvan; Adasme-Carreño, Francisco; Kasai, Daisuke; Andler, Rodrigo (Frontiers in Bioengineering and Biotechnology, 2025)
Latex clearing protein (Lcp) is a crucial enzyme in the oxidative degradation of poly(cis-1,4-isoprene), the main component of natural rubber (NR). Despite significant biochemical advances, to date, the kinetic behavior of Lcp from Streptomyces sp. K30 (LcpK30) has not been characterized, limiting the efficiency of NR conversion. In this work, LcpK30 was produced in Escherichia coli BL21 (DE3) + p4782.1::lcpK30 with L-rhamnose as the inducer, yielding 6.05 mg/L of purified protein. Kinetic assays demonstrated a positive correlation between the initial reaction rate and poly(cis-1,4-isoprene) concentration, reaching a maximum rate of 7.05 nmol O2/min at the enzyme’s saturation point, corresponding to 5 μg Lcp/mg NR. The Michaelis–Menten constant (Km) was determined to be 308.3 mg/mL, with the Hill model providing the best fit for the data. NR-to-oligoisoprenoid conversion reached 12.9 mg in 24 h, exceeding previously reported yields, while gel permeation chromatography analysis indicated conversion efficiencies over 80%, far exceeding the reports of previous studies where only 30%–40% conversions were achieved. Furthermore, Fukui function analysis suggested that the aldehyde terminal groups of the oligoisoprenoids may be less susceptible to enzymatic degradation, which would explain the mass distribution of the degradation products.